Adaptasi dan Validasi Instrumen School Bystander Behaviour Scale (SBBS) untuk Siswa SMP: Analisis Rasch Model: (Adaptation and Validation of The School Bystander Behaviour Scale (SBBS) Instrumen for Junior High School Students: Rasch Model Analysis) - Diky Zulkiflismin Zuhri; Widyastuti Widyastuti (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Bullying in junior high schools involves not only perpetrators and victims but also bystanders whose responses shape peer dynamics. Specific Background The School Bystander Behaviour Scale (SBBS) was developed to classify students as passive bystanders, defenders, or probully, yet it has not been adapted for Indonesian contexts. Knowledge Gap No prior study in Indonesia has examined SBBS using Rasch Model analysis. Aims This study aimed to adapt SBBS into Indonesian and evaluate its psychometric properties among 251 Grade 7–9 students using proportionate stratified random sampling. Results The adapted scale demonstrated adequate unidimensionality and excellent item reliability, although several items showed misfit statistics and low discrimination, while person reliability remained weak. Wright map analysis revealed item gaps and limited respondent ability variation, indicating the need for item refinement. Novelty This research provides the first Indonesian SBBS adaptation assessed through Rasch Model, offering detailed evidence on item functioning and respondent consistency. Implications The findings support the preliminary use of SBBS for measuring bystander behaviour in Indonesian junior high schools while highlighting the necessity of revising problematic items and improving data collection procedures to strengthen future applications. Keywords: School Bullying, Bystander Behaviour, Rasch Model, Instrument Adaptation, Junior High Students Key Findings Highlights: Several items require revision due to misfit and weak discrimination. Item reliability was excellent, while respondent consistency remained low. Wright map revealed gaps in item difficulty across student ability levels.